182 Ultra-Early (<12 Hours) Decompression Improves Recovery After Spinal Cord Injury Compared to Early (12-24 Hours) Decompression. (1st August 2016) - Burke, John Frederick; Yue, John K.; Ngwenya, Laura Benjamin; Winkler, Ethan A.; Talbott, Jason; Pan, Jonathan; Ferguson, Adam; Beattie, Michael; Bresnahan, Jacqueline; Haefeli, Jenny; Whetstone, William; Suen, Catherine; et al.
Abstract: INTRODUCTION: Spinal cord injury (SCI) is a devastating condition with very few treatment options. Surgical decompression of the spine after injury has been shown to improve outcomes; however, the optimal timing of surgery is a matter of debate. METHODS: We collected data from 78 patients with SCI. Based on the time to surgical decompression, we grouped patients into an ultra-early group (decompression within 12 hours of presentation), an early group (within 12-24 hours), and a late group (>24 hours). We compared the improvement in Abbreviated Injury Scale (AIS) grade from admission to discharge in each patient group. RESULTS: The patients who received surgery less than 12 hours after presentation had a significant improvement in AIS grade from admission to discharge, as well as a higher absolute AIS grade at discharge. There was no difference in AIS grade for patients who received surgery 12 to 24 hours after presentation and those who received surgery >24 hours after presentation. CONCLUSION: These data suggest that ultra-early (<12 hours) surgery is not only superior in terms of neurological recovery, but also that early surgery (12-24 hours) is no different than later surgery (>24 hours).